A INFLUÊNCIA DO CONTEXTO URBANO NA EFICIÊNCIA ENERGÉTICA DE EDIFÍCIOS VERTICAIS - Didoné, Evelise Leite; Batista, Juliana Oliveira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This work analyzed the influence of the surrounding of office buildings on energy consumption, using existing buildings in their built environment. The study is based on computer simulations using the programs EnergyPlus and Diva-for-Rhino. The selected buildings are located in the city of Maceió with a tropical climate. For the analysis, strategies for the reduction of energy consumption were applied and the real building surroundings were modelled for the different simulation programs. The analysis were realized for inefficient buildings (Prototype case) and efficient buildings (Optimal case) through the comparison of their annual energy consumption. Shadowing caused by the surrounding and solar radiation available on the envelope were evaluated through Diva-for-Rhino simulations. Results showed that shading from surrounding reduced energy consumption between 0.01% and 1.58%. Inefficient buildings presented higher reduction values. Vertical buildings in horizontal urban contexts showed less energy reduction but more solar radiation for energy generation on the envelope.